Mid- to long-term outcome of patients treated with everolimus-eluting bioresorbable vascular scaffolds: Data of the BVS registry Göttingen predominantly from ACS patients. (1st May 2017) - Hellenkamp, Kristian; Becker, Alexander; Gabriel, Yannick D.; Hasenfuß, Gerd; Hünlich, Mark; Jacobshagen, Claudius; Schillinger, Wolfgang; Schroeter, Marco R.
Abstract: Background: Bioresorbable vascular scaffolds (BVS) are widely used in routine clinical practice. While previous studies reported acceptable short- to midterm outcome after BVS implantation, data on longer-term outcome are rare. Methods: Patients treated with at least one Absorb®-BVS were consecutively enrolled. Follow-up data were assessed after 834.0 [769.0–1026.0] days. The primary device-oriented composite endpoint (DOCE) was defined as cardiovascular death, myocardial infarction (MI) and/or target lesion revascularization (TLR). Results: Between 2012 and 2014, 195 patients were included into study analysis. Overall, 244 BVS were implanted. Mean patient age was 64.0[54.3–74.0] years. Three-quarter of patients had an ACS; of those 42.9% had ST-elevation-MI and 40.8% had non-ST-elevation-MI. DOCE occurred in 3.1%, 6.7%, 11.8% and 15.4% of patients during hospital stay, within 6-months, 18-months or during the complete follow-up period, respectively. In those patients, median time until DOCE was 211.5[43.25–567.25] days. In 11 (36.7%) patients DOCE occurred after > 12 months. Using univariable analysis, bifurcation stenting was associated with a hazard ratio (HR) of 11.8[2.38–58.57] for TLR ( p = 0.002) and 2.1[1.02–4.49] for DOCE ( p = 0.045). Similarly, in ACS patients, bifurcation stenting was associated with an increased risk for TLR (HR = 10.4[2.01–53.56]; p = 0.005) and for DOCE (HR = 2.4[1.09–5.32]; p = 0.029) and in multivariable analysis, it remained an independent predictor of DOCE (HR = 3.0; p = 0.018). Conclusions: Although, the rates of (potentially) device-related complications following BVS implantation are acceptable, they are nonetheless not negligible. Interestingly, they did not decline over time. Bifurcation stenting could be found as relevant procedure-related predictor of DOCE, especially in ACS patients. Randomized trials are warranted to confirm these findings.